2020
DOI: 10.1242/dev.186619
|View full text |Cite
|
Sign up to set email alerts
|

De novo enteric neurogenesis in post-embryonic zebrafish from Schwann cell precursors rather than resident cell types

Abstract: The enteric nervous system (ENS) is essential for normal gastrointestinal function. Although the embryonic origin of enteric neurons from the neural crest is well established, conflicting evidence exists regarding postnatal enteric neurogenesis. Here, we address this by examining the origin of de novo neurogenesis in the postembryonic zebrafish ENS. Although new neurons are added during growth and after injury, the larval intestine appears to lack resident neurogenic precursors or classical glia marked by sox1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 63 publications
2
46
1
Order By: Relevance
“…The her4.3 + cells were defined as neural crest derived, post-migratory cells that retain proliferative and neurogenic potential throughout life (McCallum et al, 2020 ). An independent study, also reported the presence of neurogenic precursors in adult zebrafish, that lack expression of the canonical “glial marker” Gfap (El-Nachef and Bronner, 2020 ). They performed lineage tracing and found that these enteric glia were not derived from the vagal neural crest, but from the trunk neural crest, more specifically the Schwann cell precursors (El-Nachef and Bronner, 2020 ).…”
Section: Zebrafish As a Model Organism To Study The Ensmentioning
confidence: 97%
See 1 more Smart Citation
“…The her4.3 + cells were defined as neural crest derived, post-migratory cells that retain proliferative and neurogenic potential throughout life (McCallum et al, 2020 ). An independent study, also reported the presence of neurogenic precursors in adult zebrafish, that lack expression of the canonical “glial marker” Gfap (El-Nachef and Bronner, 2020 ). They performed lineage tracing and found that these enteric glia were not derived from the vagal neural crest, but from the trunk neural crest, more specifically the Schwann cell precursors (El-Nachef and Bronner, 2020 ).…”
Section: Zebrafish As a Model Organism To Study The Ensmentioning
confidence: 97%
“…The Tg(− 8.3phox2bb :keade) em2tg and Tgbac( phox2bb :eGFP) w37tg reporter lines are frequently used by us and are the most common ones to study the ENS, as they mark all NCCs, including migrating ENCCs and differentiated enteric neurons (Harrison et al, 2014 ; Boer et al, 2016 ) ( Figure 2A ). Alternatively, NCCs and enteric neurons can be labeled using the SAGFF234A gal4 enhancer trap line (Asakawa and Kawakami, 2009 ), whereas the sox10 reporter line labels only early progenitors (El-Nachef and Bronner, 2020 ), and the neural-specific beta tubulin (NBT) promotor labels enteric neurons but not NCCs (Peri and Nusslein-Volhard, 2008 ; Heanue et al, 2016 ). Specific neuronal subsets can also be labeled using neurotransmitter reporter lines, for example the chata reporter line, in which differentiating enteric neurons are labeled (Nikaido et al, 2018 ).…”
Section: Zebrafish As a Model Organism To Study The Ensmentioning
confidence: 99%
“…Despite opposing results, both studies found similar glial typic markers expressed by their enteric neural precursor cells: p75 NTR , Gfap , S100β , and Sox10 [ 130 ] vs. Nestin , p75 NTR , partially Gfap or S100β but not Sox10 [ 131 ]. Others reported adult neurogenesis to occur in vivo only upon stimulation of the 5-HT receptor and chemical or mechanical injury [ 132 , 133 , 134 , 135 , 136 ]. It remains to be investigated if there exists a difference between normal healthy homeostasis and disease or if it is due to the experimental set-up.…”
Section: Neurons and Glial Cells In The Adult Ensmentioning
confidence: 99%
“…Generally, ENS formation from NCCs is conserved in higher vertebrates. In zebrafish, new neurons are generated exclusively by SCPs during growth or after injury [ 136 ]. In evolutionary terms, SCPs might be the primary source for enteric neurons [ 139 ].…”
Section: Neurons and Glial Cells In The Adult Ensmentioning
confidence: 99%
“…Interestingly, SCP-driven enteric neurogenesis is evident in a postnatal ENS injury model, where SOX10 + cells give rise to the enteric neurons in adult mice during regeneration [ 17 ]. The most recent finding indicates that in post-embryonic zebra fish SCPs associated with the extrinsic gut innervation but not the enteric resident precursor cells are responcible for de novo neurogenesis [ 96 ].…”
Section: A Significant Part Of the Enteric Nervous System Is Scp-derimentioning
confidence: 99%